2021
DOI: 10.1093/ofid/ofab175
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Capnocytophaga Infection: 10 Years of Experience

Abstract: Background Capnocytophaga is a Gram-negative, facultative anaerobe. Human infection is rare but can lead to devastating outcomes. C. canimorsus can cause sepsis following an animal bite, whereas human-oral associated Capnocytophaga infections were reported in immunocompromised patients. Current data on these infections is not robust. Our goal is to provide a contemporary description of a unique characteristic of Capnocytophaga infections. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…Chesdachai et al . 1 found that meningitis associated with Capnocytophaga bacteremia primarily occurs in immunocompromised patients. Capnocytophaga infection may cause a life-threatening condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chesdachai et al . 1 found that meningitis associated with Capnocytophaga bacteremia primarily occurs in immunocompromised patients. Capnocytophaga infection may cause a life-threatening condition.…”
Section: Discussionmentioning
confidence: 99%
“…Capnocytophaga canimorsus is a fastidious, fermenter, capnophilic, facultative anaerobic, fusiform or filamentous gram-negative rod found in the commensal oral microbiota of dogs and cats 1 . It was first reported as a cause of meningitis and septicemia in the 1970s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nearly 500 documented cases of C. canimorsus infection as of 2014, the fatality rate was approximately 6.2% to 26% [1,7,8]. A variety of clinical presentations have been described, with the most common being sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Other reported clinical presentations include meningitis, endocarditis, cellulitis, and eye infections [1]. Infections with the organism are typically treated with beta-lactam/beta-lactamase inhibitor, 3 rd /4 th generation cephalosporins, or carbapenems [6,7]. Our case illustrates a less common presentation of Capnocytophaga infection presenting with mild constitutional symptoms and an urticarial exanthem in a patient with history of a dog bite that occurred several weeks prior to the patient first seeking medical attention, diabetes, but no specific immunocompromising factors.…”
Section: Discussionmentioning
confidence: 99%